THE EFFECT OF SERVICE QUALITY AND PRODUCT QUALITY ON CUSTOMER SATISFACTION AT HAIDILAO RESTAURANTS IN JAKARTA - Theophila, Bena Tria; Hapsari, Ajeng Andirani (International Humanities and Applied Science Journal, 2025)
Increasingly fierce competition in the restaurant industry requires every business operator to provide superior service and product quality in order to maintain customer satisfaction and loyalty. Haidilao, as one of the hotpot restaurants, faces challenges in maintaining service and product quality amid rising consumer satisfaction.The purpose of this study is to ascertain how customer satisfaction among Haidilao consumers in Jakarta is impacted by the quality of the products and services provided. Purposive sampling and a survey method are two quantitative approaches used in this research. 391 individuals who have made purchases at Haidilao within the previous six months participated in this study. Multiple linear regression was used in the analysis to examine each variable's partial and simultaneous influence. The findings demonstrated that, partially and concurrently, service and product quality had a favorable and considerable impact on customer satisfaction. These results demonstrate that enhancing the quality of the products and services offered is a crucial tactic for raising patron satisfaction at restaurants such as Haidilao.